Mid-infrared light-induced photoacoustic wave in water and its application. (1st January 2023) - Tsubouchi, Masaaki; Endo, Tomoyuki; Itakura, Ryuji
Abstract: We demonstrate photoacoustic (PA) wave generation at an air–water interface using a mid-infrared (MIR) laser pulse and observe its propagation in liquid water by shadowgraph imaging. The PA wave reaches a depth of more than 4 mm, which is over 100 times deeper than the penetration depth of MIR light in water. As one of the applications of the PA wave, we quantitatively analyze the ethanol mole fraction in a water–ethanol mixed solution. We achieve the generation of PA waves induced by a compact MIR laser system, which provides a new tool for imaging and inspecting the object in water.